Outcomes with FOLFIRINOX for Borderline Resectable and Locally Unresectable Pancreatic Cancer - Boone, Brian A. (2013)
BACKGROUND: Trials examining FOLFIRINOX in metastatic pancreatic cancer demonstrate higher response rates compared to gemcitabine-based regimens. There is currently limited experience with neoadjuvant FOLFIRINOX in pancreatic cancer. METHODS: Retrospective review of outcomes of patients with borderline resectable or locally unresectable pancreatic cancer who were recommended to undergo neoadjuvant treatment with FOLFIRINOX. RESULTS: FOLFIRINOX was recommended for 25 patients with pancreatic cancer, 13 (52%) unresectable and 12 (48%) borderline resectable. Four patients (16%) refused treatment or were lost to follow up. 21 patients (84%) were treated with a median of 4.7 cycles. 6 patients (29%) required dose reductions secondary to toxicity. 2 patients (9%) were unable to tolerate treatment and 3 patients (14%) had disease progression on treatment. 7 patients (33%) underwent surgical resection following treatment with FOLFIRINOX alone, 2 (10%) of which were initially unresectable. 2 patients underwent resection following FOLFIRINOX + stereotactic body radiation therapy (SBRT). The R0 resection rate for patients treated with FOLFIRINOX +/− SBRT was 33% (55% borderline resectable, 10% unresectable). A total of 5 patients (24%) demonstrated a significant pathologic response. CONCLUSIONS: FOLFIRINOX is a biologically active regimen in borderline resectable and locally unresectable pancreatic cancer with encouraging R0 resection and pathologic response rates.